Indice de riesgo sistemico de heladas (Irish) - Fernandez Long, M.E.=700 1 Murphy, G.; Torterolo, M.K.
(Es, En)
ilus., 10 ref.
Keywords: HELADA; RIESGO; CAMBIO CLIMATICO; CULTIVO; VENEZUELA; AGRONOMIA TROPICAL